Enhancing upgraded solar still performance in summer and winter through nanofluid-based solar collectors - Jagteshwar Singh; Madhup Kumar Mittal; Vikrant Khullar (Desalination and Water Treatment)
Nanofluid-based upgraded solar still had its day and nighttime performance evaluated while it was in the sunshine during the summer and winter seasons. At various points throughout the day, basin water was heated by both the solar pond and a nanofluid-based volumetrically absorbing solar collector (NBSC). The comparison of paraffin oil-based surface absorption solar collectors demonstrates that volumetric heating and surface heating work together to boost distillate yield. Sensible heat storage in the NBSC benefits from volumetric heating. The performance of upgraded stills using paraffin oil-based solar collectors (PBSC) and nanofluid-based solar collectors (NBSC) was superior to that of the traditional (reference) stills at basin water depths of 30, 40, and 50 mm. Using 40 mm BWD (Basin Water Depth) in conjunction with NBSC, the upgraded still's maximum efficiency, and productivity were 35.65% and 5.15 l/m2, respectively. The typical winter and summer day distillate produced by the upgraded stills attached with NBSC and solar pond was found to be 2.05 L/m2/day and 4.62 L/m2/day, respectively. The diurnal and nocturnal distillate produced during summer experiments was 144.02% and 64.52% higher than in winter.